Imaging of shoulder arthroplasties and their complications: a pictorial review - Damien Combes; Romain Lancigu; Patrick Desbordes de Cepoy; Filippo Caporilli-Razza; Laurent Hubert; Louis Rony; Christophe Aubé (Insights into Imaging, 2019)
Abstract Currently, an increasing number of patients benefit from shoulder prosthesis implantation. Radiologists are therefore more often confronted with imaging examinations involving shoulder arthroplasty, whether during a dedicated examination or incidentally. Standard radiography is the first-line imaging modality in the follow-up of these implants, before the possible use of cross-sectional imaging modalities (computed tomography and magnetic resonance imaging), ultrasound, or nuclear medicine examinations. Shoulder arthroplasties are divided into three categories: reverse shoulder arthroplasty, total shoulder arthroplasty, and partial shoulder joint replacement (including humeral hemiarthroplasty and humeral head resurfacing arthroplasty). Each of these prostheses can present complications, either shared by all types of arthroplasty or specific to each. Infection, periprosthetic fractures, humeral component loosening, heterotopic ossification, implant failure, and nerve injury can affect all types of prostheses. Instability, scapular notching, and acromial fractures can be identified after reverse shoulder arthroplasty implantation. Glenoid component loosening and rotator cuff tear are specific complications of total shoulder arthroplasty. Progressive wear of the native glenoid is the only specific complication observed in partial shoulder joint replacement. Knowledge of different types of shoulder prostheses and their complications’ radiological signs is crucial for the radiologist to initiate prompt and adequate management.